Comparative Evaluation of the Efficacy of Combined Intramedullary Pinning with K-Wires Pinning in the Treatment of Fifth Metacarpal Neck Fractures versus Conventional Techniques—K-Wires Pinning and Intramedullary Pinning - Dong-Eun Kim; Tong-Joo Lee; Yeop Na; Ye-Geon Noh (Medicina, 2023)
Background and Objectives: Since the neck is the weakest part of the metacarpals, the most common metacarpal fracture is a neck fracture, a type which accounts for 38% of all hand fractures. Such fractures can be fixed using a variety of conventional techniques, including intramedullary pinning and K-wire pinning. However, conventional techniques involve complications, such as angulation, stiffness, and rotational deformity. The purpose of this study was to compare the usefulness of our new technique, combined intramedullary pinning with K-wire pinning (IPKP), with those of intramedullary pinning (IP) and K-wire pinning (KP). Materials and Methods: This was a single-center, randomized controlled trial conducted between January 2005 and April 2023. A total of 158 patients with acute displaced fractures of the fifth-metacarpal neck were randomly assigned to either the IPKP group (n = 48), the KP group (n = 60), or the IP group (n = 50). We radiographically evaluated angulation and shortening in three visits: pre-operatively, post-operatively, and at a 1-year follow-up. We clinically evaluated the ranges of motion and Quick-DASH scores to assess daily living performance and the cosmetic scores, using the SBSES score, to assess patients’ satisfaction with their cosmetic outcomes. Results: The IPKP group was superior to the KP group and the IP group regarding radiographical and clinical assessments at the 1-year follow-up visit. The angulation was 15.7° (±7.7) in the KP group, 17.0° (±5.9) in the IP group, and 12.6° (±2.5) in the IPKP group (p < 0.001) at the 1-year follow-up visit. The shortening was 0.9 mm (±0.3) in the KP group, 1.4 mm (±0.2) in the IP group, and 0.4 mm (±0.1) in the IPKP group (m < 0.001) at the 1-year follow-up visit. The TAM was 272.6° (±17.5) in the KP group, 271.1° (±18.0) in the IP group, and 274.1° (±14.9) in the IPKP group (p = 0.42). Four patients (6.6%) in the KP group and two patients (4%) in the IP group were reported as having stiffness, while no patients were found to have stiffness in the IPKP group. The average Quick-DASH score was 2.3 (±0.5) in the KP group, 2.5 (±0.4) in the IP group, and 1.9 (±0.4) in the IPKP group (p > 0.05). The average cosmetic score was 3.7 (±1.2) in the KP group, 3.8 (±0.9) in the IP group, and 4.7 (±0.8) in the IPKP group (p < 0.001). A complication involving nonunion occurred in one case (1.6%) in the KP group, while there were three cases (6%) of rotational deformity in the IP groups. Conclusions: With the IPKP technique, accurate reduction can be achieved to improve hand function and cosmetic outcomes.